Papal witchcraft: the charges against Benedict XIII - Harvey, Margaret M. (Studies in church history, 1973)
The charges with which I shall deal in this paper were almost certainly a tissue of nonsense. Indeed a recent - hostile - account dismisses them as containing motifs presque folkloriques rappellant la legende de Sylvestre II. The folklore is itself interesting however, and so are the circumstances in which it could be delivered solemnly as fact to auditors at a general council by a powerful group including doctors of law and even a cardinal.The circumstances in which the charges were brought were as follows: In 1409 popes Gregory XII and Benedict XIII were tried by the council of Pisa, with the intention of deposing them to end the schism. First, 37 charges were brought against them, giving a fairly detailed and damning account of the recent behaviour of both in failing to keep their oaths to end the schism. Some members of die council must have felt that these charges were not adequate, however, because on 17 May 1409 the council gave permission for new charges to be added if necessary. Ten new charges were indeed prepared and heard from May 27-30, so we have the full account of the evidence of the witnesses. Among these charges are accusations of witchcraft against each pope.